2014
DOI: 10.18227/1982-8470ragro.v8i2.1469
|View full text |Cite
|
Sign up to set email alerts
|

Semeadura em fileira dupla e espaçamento reduzido na cultura da soja.

Abstract: Resumo -Ajustes no arranjo espacial das plantas de soja podem refletir em aumentos significativos na produtividade de grãos, sem alterações na sustentabilidade dos sistemas de produção. Objetivou-se com o presente trabalho avaliar o desempenho da cultivar de soja BRS 294 RR cultivada em fileira dupla e espaçamento reduzido, em diferentes densidades de semeadura. O experimento foi realizado a campo, em Londrina, PR, durante o período de novembro de 2011 a março de 2012. Utilizou-se o delineamento de blocos comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
24

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 15 publications
2
25
0
24
Order By: Relevance
“…This causes physiological changes in the plant, leading to premature leaf fall and yield reduction (EMBRAPA, 2013) and may have limited the magnitude of crop response to spatial arrangements. Procópio et al (2014), working with the cultivar BRS 294 RR, concluded that seeding in twin rows promotes grain yield similar to that of the traditional arrangement used in the crop. On the other hand, Vitorino (2013) worked with twin-and single-row arrangements and observed a significant yield increase of 7.6% using twin rows.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This causes physiological changes in the plant, leading to premature leaf fall and yield reduction (EMBRAPA, 2013) and may have limited the magnitude of crop response to spatial arrangements. Procópio et al (2014), working with the cultivar BRS 294 RR, concluded that seeding in twin rows promotes grain yield similar to that of the traditional arrangement used in the crop. On the other hand, Vitorino (2013) worked with twin-and single-row arrangements and observed a significant yield increase of 7.6% using twin rows.…”
Section: Resultsmentioning
confidence: 98%
“…Regarding the effect of row spacing, there are conflicting results in the literature, showing that the response is dependent on cultivar and growing environment (Rambo et al, 2003;Heiffig et al, 2006;Procópio et al, 2014). Janovicek et al (2005) reported that twin-row arrangements in direct planting systems often increased yields over those obtained with single 76-cm rows, with yields that were similar to those obtained with sowing in 38-or 19-cm rows.…”
Section: Resultsmentioning
confidence: 99%
“…O número de grãos por vagem e a massa de mil grãos não foram alterados pelas intensidades de pastejo, indicando que são componentes de rendimento pouco afetados pelo ambiente. Adicionalmente, o índice de colheita aparente não foi influenciado pelas intensidades de pastejo, obtendo-se valores próximos de 0,50, similar aos alcançados em outros trabalhos (PROCÓPIO et al 2014;BALBINOT JUNIOR et al 2015). Em função da reduzida variação nos componentes de rendimento, a produtividade da soja foi similar entre as intensidades de pastejo.…”
Section: Resultsunclassified
“…Management practices, such as sowing period, choice of the cultivar and the spatial arrangement of the plants may alter growth and grain yield (Mauad et al, 2010;Procópio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%